Iranian Women, Iranian Cinema: Negotiating with Ideology and Tradition - Moradiyan-Rizi, Najmeh (The journal of religion and film, 2015)
Throughout the ruptures of Iran’s history, Iranian women have been at the core of any social and political changes and challenges. In this historical context, Iranian women’s body, sexuality, and individuality have been confined within the constitution of religion and tradition. In recent years, however, the new generation of Iranian women is negotiating the notions of femininity, sexuality, and modernity in Iran’s society. Along with this negotiation, Iranian cinema, as the visual showcase of Iranian culture and society, has recently represented an unprecedented portrayal of Iranian women on the screen. This portrayal stems from the gender consciousness of Iranian women who are transgressing the boundaries of gender segregation and inequality. This study, therefore, provides an insight into the social and sexual changes of Iranian women’s lives in today’s Iran and analyzes the representation of these changes in Iranian post-revolutionary cinema, especially the recent decade.